Comparison of the Effectiveness and Durability of Mentalization-Based Treatment and Dialectical Behavior Therapy on Self-Injury in Adolescents with Self-Harming Behaviors - Mahdavi, Mahdieh; Amini, Naser; Keykhosravani, Moloud (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness and durability of the effects of Mentalization-Based Treatment (MBT) and Dialectical Behavior Therapy (DBT) on self-injury in adolescents with self-harming behaviors.Methods and Materials: This applied study employed a quasi-experimental pretest–posttest design with a control group and a three-month follow-up period. The statistical population consisted of all adolescents aged 13 to 18 years with self-harming behaviors who were referred to counseling and psychological service centers in District 20 of Tehran during the second half of 2024. The research sample included 45 participants who were selected through purposive sampling and, after matching, were randomly assigned to three groups of 15 participants each: Mentalization-Based Treatment, Dialectical Behavior Therapy, and control. The experimental groups received 12 weekly 60-minute sessions of Mentalization-Based Treatment and 12 weekly 60-minute sessions of Dialectical Behavior Therapy, respectively, whereas the control group received no intervention. Data were collected using the Self-Injurious Thoughts and Behaviors Interview developed by Klonsky and Glenn (2009). Data were analyzed using mixed repeated-measures analysis of variance and Bonferroni post hoc tests in SPSS-26.Findings: The results indicated that the main effect of group on self-injury was not statistically significant (F = 0.617, p = .544, ηp² = .029); however, the main effect of time (F = 7.27, p = .008, ηp² = .148) and the interaction effect of time and group (F = 4.59, p = .042, ηp² = .107) were statistically significant. Bonferroni post hoc test results at the posttest stage showed that a significant difference existed only between the Dialectical Behavior Therapy group and the control group (padj = .016), whereas the differences between the Mentalization-Based Treatment group and the control group, as well as between the two treatment groups, were not statistically significant. Furthermore, pairwise comparisons across time demonstrated that only the Dialectical Behavior Therapy group showed significant differences between pretest and posttest (padj = .022) and between pretest and follow-up (padj = .034), whereas no significant changes were observed in the Mentalization-Based Treatment group or the control group.Conclusion: Based on the findings, Dialectical Behavior Therapy was more effective than Mentalization-Based Treatment in reducing self-injury among adolescents with self-harming behaviors, and its effects remained stable through the follow-up phase. In contrast, Mentalization-Based Treatment did not produce a statistically significant reduction in self-injury in the present study. Therefore, Dialectical Behavior Therapy may be considered a more effective intervention for reducing and stabilizing improvement in self-injurious behaviors among this group of adolescents.